2010
DOI: 10.1002/iroh.201011250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Techniques to Assess Surface and Subsurface Streambed Colmation with Fine Sediments

Abstract: International audienceMethods commonly used to assess physical colmation are mainly based on observations of streambed surface. These methods have been widely used but remain relatively subjective because of the observer effect. Visual estimation, penetrometry, hydraulic conductivity and wooden stake methods were applied to assess colmation conditions on 9 reaches with the objective of comparing them with the direct measurement of fine sediment content in subsurface habitat using the freeze coring method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 61 publications
0
51
0
Order By: Relevance
“…In addition, the variety of sediment management among dams (e.g., timing of flushing operations) may obscure any effect. Extending our study to reaches bypassed by dams or situated just downstream is likely to provide different results (Descloux et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the variety of sediment management among dams (e.g., timing of flushing operations) may obscure any effect. Extending our study to reaches bypassed by dams or situated just downstream is likely to provide different results (Descloux et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Fine sediment is supplied from scour of the upstream streambed or banks, and from erosion within the catchment (Wood and Armitage, 1997). Worldwide, land clearance, logging, and mining have increased catchment fine sediment supply whilst sediment control, sand mining, and trapping with dams offsets some of these increases (Walling, 2006;Descloux et al, 2010;Datry et al, 2014).…”
Section: Conceptual Model Of Streambed Hydraulic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In their clinal model of interstitial communities, Brunke and Gonser () showed that the colonisation of shallow sediment layers by groundwater taxa was restricted by interference competition with surface water taxa. And last, the formation of a coarse, immobile surface layer in the most sediment supply‐limited channels can promote interstitial clogging by reducing bedload movement during floods and hence the remobilisation of fine sediments deposits (Descloux, Datry, Philippe, & Marmonier, ). Clogging may severely increase the resistance of the hyporheic corridor to the movement of interstitial organisms because it reduces the pore space available to organisms as well as the structural connectivity between pores (Datry, Lamouroux, Thivin, Descloux, & Baudoin, ; Descloux, Datry, & Marmonier, ; Nogaro, Datry, Mermillod‐Blondin, Descloux, & Montuelle, ).…”
Section: Discussionmentioning
confidence: 99%
“…The freeze‐coring technique was used to measure the effective porosity in the bed‐sediment of each river (Descloux et al ., ). Before core extraction, the freezing operation required the injection of about 25 L of liquid nitrogen for 15 min.…”
Section: Methodsmentioning
confidence: 99%